Can taxes stabilize the economy in the presence of consumption externalities? - Teresa Lloyd-Braga; Leonor Modesto (Institute for the Study of Labor (IZA), 2012)
Considering a finance constrained economy, we discuss the stabilization role of variable labour and capital income taxes under a balanced-budget rule in the presence of consumption externalities of the keeping up with the Joneses type. We find that sufficiently procyclical labor and/or capital income taxes are able to ensure saddle path stability eliminating belief-driven cyclical fluctuations. Moreover, for higher values of consumption externalities, saddle path stability can only be reached with more procyclical labor or capital income taxation. We therefore conclude that finance constrained models with keeping up with the Joneses preferences call for traditional Keynesian demand-management policies in order to stabilize business cycle fluctuations.
Keywords: E32; E62; 330; indeterminacy; consumption externalities; capital and labor income taxation; Lohnsteuer; Kapitalertragsteuer; Globalsteuerung; Konsuminterdependenz; Gleichgewichtsstabilität; Theorie